Cardiac Computed Tomography Coronary Angiography Post Non-diagnostic or Equivocal Myocardial Perfusion SPECT - Abdullah Al-harbi; Mervat M Aboulkheir; Ahmed Fathala (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2017)
Background: Myocardial perfusion single- photon emission computed tomography (MP-SPECT) plays a key role in the management of patients with known or suspected coronary artery disease (CAD).However, Infrequently, MP-SPECT is non-diagnostic or equivocal. Computed Tomography coronary angiography (CTCA) has high diagnostic accuracy and excellent negative predicted value .The goal of the study is to investigate the diagnostic value of CTCA after non-diagnostic, equivocal, and or borderline abnormal MP-SPECT. Methods: 64 patients were with suspected CAD were enrolled in this study, the mean age was 51  24 years, 36 (56%) male and 28 (44%) female. MP-SPECT result was classifi ed into 3 categories: Probably normal or probably abnormal, Abnormal function and normal myocardial perfusion, and equivocal or nondiagnostic. Results: Probably normal/ abnormal MP-SPECT: 23 (36%) patients, abnormal function with normal MP-SPECT: 10 patients (16%), equivocal and /or non-diagnostic: 31 (48%) patients. CCTA: Normal Coronary arteries: 46 (72%) patients, Mild stenosis 5 (8%) patients, Moderate stenosis: 7(11%) patients, and more than 75%: 6 (9%) patients. Patients with normal coronary and mild stenosis contributed to total of 51(80%) patients, Patients with moderate and severe stenosis 13 (20%). Obstructive CAD was found in 2 (9%), 5 (50%) and 6 (19%) in patients with probably normal or probably abnormal MP-SPECT, abnormal function and normal perfusion, and equivocal and non-diagnostic MP-SPECT respectively. Conclusion: Non-diagnostic, equivocal, or mildly abnormal MP-SPECT is infrequent but it causes a management dilemma. CTCA is essential in such clinical circumstances because the majority of such patients have normal coronary artery but few patients may require conventional coronary angiography.